Quantification of the Influence of Morphologies on Laser Cutting Quality - Maria Ramard; Romain Laniel; Mathieu Miroir; Olivier Kerbrat (Journal of Machine Engineering)
Laser cutting, a long-established multi-physical process, has been widely adopted in the metallurgical industry, but its rapid industrialization has impacted quality control. Reviews from 2008 to 2022 primarily focus on single-criterion quality approaches, targeting defects like the Heat-Affected Zone, surface roughness, or kerf geometry, rather than adopting comprehensive methods. In addition, these studies show that cutting quality can be improved by selecting laser manufacturing parameters and part parameters such as thickness or material. However, the influence of part morphology remains under-explored.